Domestikasi Teknologi Informasi dan Komunikasi Keluarga Muslim di Kampung Cyber Surabaya - Moch. Choirul Arif; Ries Dyah Fitriyah (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2019)
The aim of the research is to explain ; first, the basic argument for household muslims to domesticate information and communication technology. Second, the process of domestication of information technology. The third implication of the domestication of technology and information. This study used descriptive qualitative method with phenomenological approach. The goal is to understand the meaning behind the action naturally. The results of this study are: First, Domestication of the information and communication technology rests on reasoning awareness, that leads to understanding the meaning and function of information and communication technology for them (Purposeful actions). Second.The existence of kampoeng cyber as instrument of the process of domestication of information and communication technology. Was apparently able to bring parents and children together in cultural negotiation space. The result is a process of aproriation, objectification, incorporation and conversion which accelerate the domestication of information and communication technology. Third, Moslem family awareness of the positive and negative impact that the process of domestication of information and communication technology influences their religious and social interactions. Therefore, the Cyber Kampoeng developed is used a medium of the construction awareness and values inheritance in the next generation.